2015
DOI: 10.1002/mus.24611
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance myography in duchenne muscular dystrophy and healthy controls: A multicenter study of reliability and validity

Abstract: EIM is a reliable and valid measure of disease severity in DMD. Longitudinal studies comparing EIM with other assessments over time in DMD are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 16 publications
(25 reference statements)
3
50
0
Order By: Relevance
“…Phase angle represents the time shift of a sinusoid wave when passing through the muscle, which was previously used as a major outcome measure of EIM since it is less affected by the architecture and shape of the muscle compared with R or X (37). The smaller phase angle in the SCI group is in line with the data from a multicenter study of DMD children (38) and ALS subjects (23). Reductions in cell size and the presence of more connective tissue in the muscle also reduce the EIM phase angle (16).…”
Section: Discussionsupporting
confidence: 86%
“…Phase angle represents the time shift of a sinusoid wave when passing through the muscle, which was previously used as a major outcome measure of EIM since it is less affected by the architecture and shape of the muscle compared with R or X (37). The smaller phase angle in the SCI group is in line with the data from a multicenter study of DMD children (38) and ALS subjects (23). Reductions in cell size and the presence of more connective tissue in the muscle also reduce the EIM phase angle (16).…”
Section: Discussionsupporting
confidence: 86%
“…Training was straightforward. There was excellent inter-evaluator reliability between an experienced assay performer and a trainee (Fig 2) [35, 42, 5254]. …”
Section: Discussionmentioning
confidence: 99%
“…EIM has been extensively used as a painless and reliable outcome measurement to study various neuromuscular diseases including amyotrophic lateral sclerosis (ALS) [2027], spinal muscular atrophy [28], facioscapulohumeral muscular dystrophy [29], congenital muscular dystrophy [30], inflammatory myopathy [31], inclusion-body myositis [19, 32], radiculopathy [33], and disuse atrophy [34]. Of relevance to our study, EIM has been successfully used in DMD patients and mdx mice [3542]. These studies have revealed excellent reliability and validity of EIM as a powerful noninvasive biomarker for both pre-clinical and clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…43 The refinement of EIM to quantify changes in diseased muscle with subcutaneous fat lends its use to determine changes throughout the clinical spectrum in Pompe disease patients in addition to its current use in patients with related neuromuscular disorders. 41,4448 …”
Section: Discussionmentioning
confidence: 99%